¿Puede el acoso escolar generar depresión en las víctimas? la relación entre acoso escolar y depresión en estudios longitudinales y retrospectivos - Portocarrero Salcedo, Lucía del Carmen (2024)
Bullying is common and several studies have reported harmful consequences of this aggressive behavior, including depression. The aim of the present investigation was to determine whether there is a causal relationship between bullying and depression by reviewing longitudinal and retrospective studies from the last 5 years. The PRISMA guide was followed to carry out a search in the Scopus, Scielo and Web of Science databases, following eligibility criteria. Ten empirical investigations that met the inclusion and exclusion criteria determined for the study were selected for the analysis. It was found that there is a positive causal relationship between bullying and depressive symptoms, but there are also findings that refer to a circular relationship between both variables. Finally, the most important results, their practical implications for the work of the educational psychologist, as well as limitations and recommendations are discussed.